ANALISIS PENERAPAN HOSPITALITY, HYGINE DAN SANITASI PADA USAHAKULINER DIKAWASAN WISATA SETU BABAKAN DI JAGAKARSA JAKARTA SELATAN - Wiriadi Sutrisno; Siswi Wulandari; Nur Sodik (JABE (Journal of Applied Business and Economic), 2016)
The success    key   to    culinary business  is not  only depend    on quality products, but also on  other significat  factors  such as    hospitality, hygiene and sanitation  are said as   HHS in running the culinary business   getting succes. However, those    three factors, don’t put on    serious attention, especially for the  Business  Actor Micro (PUM), who worked in the food    as well as culinary business, even for the beginers as well as the experieinced one,    especially in tourist areas Setu Babakan, South Jakarta. Therefore,suppose HHS practices in operations will   not be  optimalize, in the long term, these conditions would have a negative impact  to  culinary business as well as the tourism business overall  in Setu Babakan. PUM in Setu Babakan,’s  donethe  businessjust  on conventionally based. They run  all processing  steps,  start from  raw materials handler    to the serving     to the customer,   just   ignoring    the HHS  factors. Processed foods that will be served directly to customers, is still done by gloveless.  Similarly, where  all  kitchen workers are not using an apron, which limits to groceries vulnerable infestation microbiology and  mor that those,  there is no hospitality in serving as well ingreating to the customers. This study aims to find out how to PUM be aware that HHS is very important in business they are doing and how  toform  suitable  training    for the PUM (Training Need Assesment/TNA), so they can run  the culinary business by applying HHS firmly as well.